Attracting New Talent to the Governmental Public Health Workforce: Strategies for Improved Recruitment of Public Health Graduates. Issue 1 (2nd January 2022) - Locke, Rachel; McGinty, Meghan; Guerrero Ramirez, Grace; Sellers, Katie
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context: Governmental public health (GPH) agencies need a diverse, skilled, and motivated workforce to advance health and well-being, but they face a number of recruitment challenges. While there has been massive growth in public health degree programs and graduates, those with a degree in public health are underrepresented in the GPH workforce. Objectives: This study evaluates potential reasons undergraduate and graduate public health degree holders are underrepresented in the GPH workforce, assesses student awareness of and interest in GPH jobs, and identifies strategies for improved recruitment. Design: We conducted pilot focus groups to explore public health students' interest in working for GPH agencies, obstacles to employment, and how this career path could be better promoted. Setting and participants: Eight focus groups were conducted with a total of 33 participants at 3 universities and at the Annual Meeting of the American Public Health Association. Participants were enrolled full-time in or graduated within the last year from a public health bachelor's degree program or a public health master's degree program. Undergraduates had declared a public health major and were in their senior year; graduate students were in their second year and actively job seeking; or participants graduated within the past 12 months. Main Outcome Measures: The focus groups sought to capture students' perspectives of GPH agencies and how they believe recruitment can be improved. Results: Participants described attractive job attributes including fulfilling, meaningful work; a position at a mission-driven organization; and the opportunity to make an impact on their community. Governmental public health agencies were viewed as bureaucratic, lacking innovation, and underresourced. Participants reported difficulties accessing and finding relevant job postings. Conclusions: Key to effectively recruiting and retaining new graduates is understanding their perceptions about/experiences with GPH agencies. While GPH jobs have desired attributes, participants reported that health departments are not effectively recruiting them.